Factors associated with the use of maternal health services by mothers in a post-conflict area of western Côte d'Ivoire in 2016 - Mamadou Samba; Akissi Régine Attia-Konan; Abou Dramane Sangaré; Gotré Jules Youan; Luc Philippe Kouadio; Ramata Bakayoko-Ly (BMC, 2020)
Abstract Background In Côte d'Ivoire, maternal health service utilization indicators remain low despite improvements in health coverage and the availability of free health care for pregnant women. The objective of the study was to identify the determinants associated with the use of maternal health services in the department of Bloléquin, in western Côte d'Ivoire. Methods We conducted a cross-sectional study with an analytical focus. The study sample size was 400 women. Study participants were selected through a two-stage cluster survey. The data were collected using a standardized questionnaire whose items concerned socio-demographic data, the different uses of maternal health services, namely childbirth assisted by a health professional, use of family planning, prenatal consultation and postnatal consultation. Logistic regression was used to investigate factors associated with the use of maternal health services. The significance of the statistical tests was set at 5%. The odds ratios and 95% confidence intervals were calculated and interpreted. Results The results showed that women made less use of family planning services (OR = 0.4), prenatal consultation (OR = 0.2) and assisted childbirth (OR = 0.2) when they provided the funding for care themselves. Women with monthly incomes above $26.8 used family planning services 4 times more than those with lower incomes. Married women used prenatal consultations 3 times more often than unmarried women (CI95% = 1.4-7.3). Desiring pregnancy increased the use of post-natal consultations by 3 times (CI95% = 1.5-6.1). Conclusion Improving the use of maternal health services in western Côte d'Ivoire requires taking into account women's socio-cultural and economic challenges. In initiatives related to the financial empowerment of women, efforts must be made at the level of emotional considerations related to pregnancy.